2018
DOI: 10.3399/bjgp18x699101
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of drug–herb and drug–supplement interactions in older adults: a cross-sectional survey

Abstract: BackgroundPolypharmacy is common among older adults, with increasing numbers also using prescription drugs with herbal medicinal products (HMPs) and dietary supplements. There is no reliable evidence from the UK on concurrent use of HMPs and dietary supplements with prescription drugs in older adults.AimTo establish prevalence of concurrent prescription drugs, HMPs, and dietary supplements among UK community-dwelling older adults and identify potential interactions.Design and settingCross-sectional survey of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
72
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 36 publications
(47 reference statements)
3
72
0
4
Order By: Relevance
“…The most popular products taken showed a low potential for drug interaction and few patients reported any adverse events. Agbabiaka, Spencer, Khanom, and Goodman () found a remarkably similar incidence (33.6%) in the elderly but identified some concerns about potential interactions. This is comparable with other Western countries.…”
Section: Introductionmentioning
confidence: 92%
“…The most popular products taken showed a low potential for drug interaction and few patients reported any adverse events. Agbabiaka, Spencer, Khanom, and Goodman () found a remarkably similar incidence (33.6%) in the elderly but identified some concerns about potential interactions. This is comparable with other Western countries.…”
Section: Introductionmentioning
confidence: 92%
“…Drug–drug interactions and food–drug interactions mediated by these two active transporters—P-gp and OATP—have been reported. In addition, a study on medication use patterns revealed that 50% of 2590 study participants had taken at least one prescription drug during the week prior to the study, and 16% of them had taken one or more herbals/supplements [ 11 , 12 ]. Given that St. John’s wort was found to increase P -gp expression [ 13 ], it is necessary to evaluate the effects of herbal supplements on these transporters.…”
Section: Introductionmentioning
confidence: 99%
“…) are prevalent, prescribed medicines, over the counter agents, and natural products including functional food components are often used concomitantly. Consequently, herb-drug interaction represents an underlying risk as some natural components may alter pharmacokinetics, efficacy, and safety of therapeutic agents (Agbabiaka et al, 2018;Briguglio et al, 2018;Parvez and Rishi, 2019). As such, investigations on disposition mechanisms of xenobiotics and their association with herb-drug interaction can provide scientific foundations for safe and effective use of various remedies.…”
Section: Introductionmentioning
confidence: 99%